Pedagoški delavci v strokovnem in poklicnem izobraževanju kot aktivni oblikovalci in usmerjevalci lastnega poklicnega razvoja - Javornik Krečič, Marija; Vršnik Perše, Tina; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2015)
Educational Professionals in VET as Active Designers and Guides of Their Own Professional Development. The paper presents part of the evaluation study results on professional development of pedagogues in vocational education. The results indicate to what extent this group of teachers are active creators and guides of their own professional development. Based on the data analysis in what fields of their professional work and in what forms of professional training they participate most frequently, one can conclude that teachers in vocational programmes are not very active creators of their own professional development. Nevertheless, it has to be pointed out that professional development of teachers in vocational education programmes has to be derived from the specificities of their situation between the spheres of education and employment and that it is therefore not possible to provide a unique guideline how to activate teachers for their own professional development.
Keywords: professional development; vocational education and training; in-service teacher training